Parents' Perception of Private Schools as a Quality Education Solution for Upper Middle Class Families in Sukoharjo Regency - Yuliyanti, Gita; Nugrahani, Dian Ahimza; Septyani, Diyas; Laeli, Binti Nurul; Istiqomah, Intan Nur; Anindhita, Az Zahra; Nurhadi, Nurhadi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Currently, education is easily accessible to all levels of society, especially the upper middle class. However, many parents tend to choose private schools over public schools to send their children to school. This is influenced by factors such as facilities and the quality of school education. This study aims to identify and analyze the factors that influence parents' preferences in choosing private elementary schools. This type of research is qualitative research. The research sample was selected by purposive sampling, namely by determining certain criteria. Data were collected through observation, interviews, and documentation. The results of the study showed that parents prefer private schools and are not burdened with spending high costs because they are comparable to what their children get at school. It can be concluded that factors such as facilities, quality of school education, character formation, and instilling religious values influence parents' decisions in choosing schools for their children. The benefits of this study are to provide an overview to the general public, especially parents, that private schools can be a superior choice in terms of quality of education, facilities provided, and religious-based programs, which can help them make the right decisions for their children's education.